Is the Cross-Section of Expected Bond Returns Influenced by Equity Return Predictors? - Chordia, Tarun (Institutional Knowledge at Singapore Management University, 2014)
This paper studies whether the commonly analyzed equity return predictors also predict corporate bond returns. Bond markets do price risk, but are also susceptible to delayed information transmission relative to equities. Firm size and profitability are negatively priced while idiosyncratic volatility is positively priced, suggesting that large firms, more profitable firms and relatively less volatile firms are more attractive to bond investors, thus requiring lower returns. Consistent with a relatively sophisticated institutional clientele, bonds are efficiently priced in that none of the behaviorally-motivated variables provide profitable trading strategies after accounting for transactions costs, though some risk-based variables continue to do so.